THE EFFECT OF GAMIFICATION ON THE MOTIVATION AND LEARNING OUTCOMES OF EIGHTH GRADE STUDENTS AT SMP NEGERI 3 LUWUK - Wahyuni Wijayanti; Novianty Djafri; Pupung Puspa Ardini; Mohamad Zubaidi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
Mathematics is a subject that is often considered difficult and boring for students. With the development of the times, a new method of teaching mathematics is needed to encourage student motivation and learning outcomes. Gamification is a teaching method that integrates game technology into learning, where students are Generation Z who are directly exposed to the digital world. The objectives of this study are: 1) to determine the differences between conventional learning methods and gamification; 2) to determine whether gamification has an effect on student motivation and learning outcomes. The method used is experimental with a pre-test post-test design. The sample consists of 170 students divided into two classes, namely the control class and the experimental class. The analysis tool used is the independent T-test. The analysis results show that 1) gamification produces a more interesting, interactive, and competitive learning experience than conventional learning methods. 2) Gamification has an effect on the motivation and learning outcomes of eighth-grade students. Keywords: gamification; learning motivation; learning outcomes